Reading Harriet Martineau in the context of social thought and social theory. - Vineeta Sinha, (Universiti Kebangsaan Malaysia, 2001)
The recorded historiography of the social sciences is steeped in androcentrism. It exclusively remembers, canonizes and lists contributions by male scholars. This mode of recalling, by and large renders invisible contributions by women thinkers in the history of ideas. In this paper I document the experience of introducing the works and contributions of Harriet Martineau (1802-1876), known to very few as the 'first woman sociologist', alongside the writings of Marx, Weber and Durkheim, to a class of undergraduates. I see this introduction as a powerful strategy for the recovery, and rightful location of women thinkers and analysts in narrating any history of the social sciences. Through the themes of androcentrism, 'female invisibility', multiplicity and difference, I also address the discourse on indigenisation in the social sciences. The latter, although it has rightly highlighted the biases and distortions in the practice of mainstream social science, has yet to place the issue of androcentrism on its agenda, a stance that makes it more similar to, rather than different from, mainstream social science theorising.